If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 + 2x = -3x + 9 Reorder the terms: -11 + 2x = 9 + -3x Solving -11 + 2x = 9 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -11 + 2x + 3x = 9 + -3x + 3x Combine like terms: 2x + 3x = 5x -11 + 5x = 9 + -3x + 3x Combine like terms: -3x + 3x = 0 -11 + 5x = 9 + 0 -11 + 5x = 9 Add '11' to each side of the equation. -11 + 11 + 5x = 9 + 11 Combine like terms: -11 + 11 = 0 0 + 5x = 9 + 11 5x = 9 + 11 Combine like terms: 9 + 11 = 20 5x = 20 Divide each side by '5'. x = 4 Simplifying x = 4
| 5x+7=7x+1 | | 7*x*1=68 | | y-x=-16 | | 180-(20x+4)+8x+8+6x+4=180 | | 4.8(x-2)=-0.2x+15.4 | | -9x+5=-4 | | 9*x*3=612 | | ax+b=2x+d | | F(x)=2x^3+9x^2+20 | | 60+-7y=-3 | | 11w+70=-7 | | 5(x-1)+45=-3x | | -2x+1=-73 | | 9x+5=-40 | | 4x-15+2x+10=43 | | 45y+6=-84 | | 2x^3+10x^2+6x=0 | | 5.5h-15=4h | | 2(1-y)+3=3(y+5) | | 4y-6-2y+5=0 | | 9+3x=612 | | 10=y-17 | | -x+3x-2=0 | | 9+3=612*x | | -1.23x=-456 | | 16x+3=18x+2 | | 2q=26 | | 11x=7x+12 | | 9+3+x=612*x | | 0.1x+0.5y=-1.3 | | 3(x-7)+20=-2+6x+1 | | 16x+3=18+2 |